Projet d'amelioration du zebu Mbororo par croisement d'absorption avec le zebu foulbe de N'gaoundere - Capitaine, P. (1971)
Describes the project on the genetic improvement of Mboro Zebu by crossbreeding with Ngaoundere West African Zebu. Topical discussions on breed characteristics, project outline and achievements of the Animal Production Service included.